Do Agile Worth: A Survey Of Three Agile Methods (Global Journals of Research in Engineering, 2012)
Agile methods are Group of software development methodologies based on iterative development, where requirements and solutions evolve through collaboration between self-organizing cross-functional teams. Today, the debate continues again about how much agile method worth? Is it really true that the software development in agile way have real advantages? As Craig Larman said as foreword in Patterns of Agile Practice Adoption, The Technical Cluster writes by Amr Elssamadisy#x201D;: #x201C;Many confuse the heart of #x2018;Agile#x2019; with practices rather than values; yet the essence of Agile methods is the four values ". The agile Manifesto describes four values, which sustain all the methods agile. This article with the help of a survey conducted in a poll of the "agile practitioners" will demonstrates until where the agile values influences the production software in a study of 3 factors : Team, Usage and Organization.
Keywords: Agile methods; software metrics; Extreme Programming; Scrum Methodologies; Lean Software Development